Being Jewish after the destruction of Gaza - Beinart, Peter (Atlantic Books, 2025)
"In Peter Beinart's view, one story dominates Jewish communal life: that of persecution and victimhood. It is a story that erases much of the nuance of Jewish religious tradition and warps our understanding of Israel and Palestine. After Gaza, where Jewish texts, history and language have been deployed to justify mass slaughter and starvation, Beinart argues, Jews must tell a new story. After this war, whose horror will echo for generations, they must do nothing less than offer a new answer to the question: What does it mean to be a Jew?Beinart imagines an alternate narrative, which would draw on other nations' efforts at moral reconstruction and a different reading of Jewish tradition. A story in which Israeli Jews have the right to equality, not supremacy, and in which Jewish and Palestinian safety are not mutually exclusive but intertwined. One that recognizes the danger of venerating states at the expense of human life." -- Publisher